2010
DOI: 10.1093/toxsci/kfq086
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure Perturbs Epithelial-Mesenchymal Cell Transition and Gene Expression In a Collagen Gel Assay

Abstract: Arsenic is a naturally occurring metalloid and environmental contaminant. Arsenic exposure in drinking water is reported to cause cancer of the liver, kidneys, lung, bladder, and skin as well as birth defects, including neural tube, facial, and vasculogenic defects. The early embryonic period most sensitive to arsenic includes a variety of cellular processes. One key cellular process is epithelial-mesenchymal transition (EMT) where epithelial sheets develop into three-dimensional structures. An embryonic proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…12 Consistently, in the process of chronic AS exposure, we noted with great interest that AS treated HT-29 cells underwent a marked morphologic change, i.e., from epithelial to spindle-like mesenchymal morphology ( Fig. 4A-C).…”
Section: Emt Is Involved In As Treated Ht-29 Cellssupporting
confidence: 74%
“…12 Consistently, in the process of chronic AS exposure, we noted with great interest that AS treated HT-29 cells underwent a marked morphologic change, i.e., from epithelial to spindle-like mesenchymal morphology ( Fig. 4A-C).…”
Section: Emt Is Involved In As Treated Ht-29 Cellssupporting
confidence: 74%
“…Since EMT enables cell to move and invade [18], we then determined the effects of CaA on the EMT process in malignant HaCaT cells. As shown in Figure 2A, malignant HaCaT cells displayed a fibroblast-like mesenchymal appearance; however, after these cells were exposed to CaA for 48 h, they showed an epithelial-like morphology.…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed that infection with adenovirus expressing GFP alone defined the basal distribution of cells as epithelial, activated, or transformed and the addition of vehicle or TGFβ2 do not alter this distribution (Fig 2C). Cell proliferation in explants is low and alterations in proliferation cannot explain the decreases in cell invasion noted in these assays ([26], and Fig 2D, E). …”
Section: 0 Resultsmentioning
confidence: 99%